The Prevention of Cardiovascular Disease in Older Adults. Issue 5 (7th February 2020) - Coll, Patrick P.; Roche, Vivyenne; Olsen, Jaclyn S.; Voit, Jessica H.; Bowen, Emily; Kumar, Manish
Abstract : Cardiovascular disease (CVD) is common in older adults. CVD is a significant cause of both death and disability in old age. Though the prevention and treatment of CVD have been extensively studied, historically older adults and especially those older than 75 years have been underrepresented in clinical investigations designed to determine the best way to prevent or treat CVD. As a result, geriatrics clinicians frequently need to decide which interventions to recommend for their patients by extrapolation from existing data, which may or may not be applicable to the patients they are caring for. This narrative review summarizes existing data regarding the prevention of three common CVDs in older adults: stroke, coronary artery disease, and peripheral artery disease. Special emphasis is given to the prevention of CVD in those aged 75 years or older. J Am Geriatr Soc 68:1098–1106, 2020